Comparison of Root Canal Filling Quality and Periapical Health Using Periapical, Panoramic, and Cone-beam Computed Tomography Radiographic Techniques - Maryam Janani; Negin Ghasemi; Masoumeh Johari; Leila Nazari (Mashhad University of Medical Sciences, 2022)
Introduction: Radiography is one of the techniques used to evaluate the quality of obturation. This study compared the quality of root canal obturation and periapical tissue using periapical and panoramic radiographs and cone-beam computed tomography (CBCT). Methods: This descriptive cross-sectional study was conducted on 138 teeth of patients referring to Tabriz Faculty of Dentistry, Tabriz University of Medical Sciences, Tabriz, Iran. The patients were in the 15-72 age range and had undergone CBCT, panoramic, and periapical x-ray examinations of their endodontically treated teeth. The patients' periapical, panoramic, and CBCT radiographs were retrieved from the faculty archives and studied. All the images and results were studied by an endodontist and a radiologist separately. Results: The results showed a significant difference between panoramic radiography and CBCT in identifying samples without voids. Panoramic radiographs showed the most samples without voids, and the CBCT method showed the least samples without voids (23.7% vs. 2.2%). The highest agreement in identifying the lesions was obtained between the panoramic and periapical methods. The CBCT technique showed the highest frequency (97.3%, P=0.003) of bone thickness changes in samples with lesions. Conclusion: Based on the results, a significant difference in the quality of root canal obturation was observed between periapical and panoramic radiographs with CBCT; however, no significant difference was observed between periapical and panoramic radiographs.